Creating New Partnerships: An Examination of Two Collaborative, Grant-funded Digitization Projects - Oleen, Jenny K.; Olsen, Livia M. S. (My University, 2010)
Acquired over a lifetime and representing that lifetime of knowledge, slides (used for class lectures, conferences, and public presentations) and extensive collections of print materials document the progress and results of a professor’s research. These materials are a valuable source of information for current and future generations. Now that digital images are the norm, scanning slides and print materials is a way to ensure that future students and researchers can access and use these unique materials. This poster will discuss the similarities and diff erences between two grant-funded, collaborative scanning projects conducted at Kansas State University. Both projects were collaborations between librarians and academic faculty. The fi rst project digitized grain sorghum disease images slides that were originally captured by Dr. Larry Clafl in, an internationally recognized expert on grain sorghum diseases. He was nearing retirement when he approached the library about preserving his grain sorghum disease slides. The project team utilized the Plant Diagnostic Information System (http://www.pdis.org/) which allows researchers to submit images of plants with pest problems into a web searchable database of diagnostic information. Protocols created during this project were later used for an additional slide digitization project which involved corn and potato disease slides. The second project involved digitizing natural history publications, now available through the web portal BiodIS (http://biodis.k-state.edu/ ), K-State’s Biodiversity Information System. BiodIS, a collaborative project between the K-State Herbarium, the Museum of Entomological and Prairie Arthropod Research, and K-State Libraries, provides online digitized biodiversity content. The portal houses databases for these K-State natural history collections, specimen photographs, sample K-12 lesson plans, and a digital resources section. A range of documents, from master’s theses to Agriculture Experiment Station Publications, have been scanned and uploaded as searchable PDF fi les. These two projects have similarities and diff erences which can be applied when considering future grant-funded collaborative digitization projects.
Keywords: Digitization; Slides; Documents; BiodIS; Collaborative projects; Archiving